Implementasi Metode Iqra dan Ilmu Tajwid dalam Pengajaran Al-Qur’an di Yayasan Shobani Islamic Centre di Desa Perbawati: Penelitian - Ihsan Nurhuda; Fauzan Fadillah; Aeni Latifah; Sarmita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Shobani Islamic Centre Foundation is an educational institution for the teaching of the Qur'an located in Borojong, Perbawati village, Sukabumi District, Sukabumi Regency-West Java. The purpose of the establishment of this Madrasah is to make early childhood to adolescence become an intelligent generation and know and be able to read the Qur'an properly and correctly. This study uses a descriptive qualitative approach in order to obtain broad and in-depth information related to the research objectives. The data sources in this study are teachers and parents of children. Data collection uses observation, observation, interview, and documentation techniques. The results of the study show that the implementation of the Iqro and Tajweed' methods in teaching the Quran to children consists of planning, implementation, and evaluation stages. The use of iqro' and tajweed methods provides a basic understanding of hijaiyah letters and ease in distinguishing and pronouncing letters properly and correctly both sequentially and randomly. The service carried out at the Ta'lim Daruttalamidil Islamiyah Council is motivated by the ability of children to read the Qur'an which is still considered inappropriate. So in this case, the researcher wants to apply the learning of the Qur'an with the Iqro method and the science of tajweed' which is expected to be able to make children more precise and appropriate in reading the Qur'an. learning of the Qur'an iqro' method and tajweed science at the Ta'lim Daruttalamidil Islamiyah Council uses a private method and question and answer, namely children read the main material in front of the teacher/KKN participant then listened to by the teacher/KKN participant and carried out in turn..